Ecological Policy in Agricultural Land Resources Using of Ukraine - Sokol, Lesia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The paper considers theoretical and practical aspects of environmental management in agriculture, especially of land resources using and sustainable development. The ecological policy of agricultural land using in Ukraine includes a lot of instruments of state regulation, legislative and normative support. However, environmental management requires further research and improvement of tools for sustainable agricultural development. The land fund structure, general protection measures of environment and financial expenses for the protection, rational using and restoration of land resources in Ukraine were analyzed. The indicators of sustainable agricultural development were considered. Information base of researches were the scientific heritage of Ukrainian and foreign scientists, materials of statistical reporting of the State Statistics Service of Ukraine, materials of personal observations of the author. In the outcome, the authors’ researches reject the proposals in creation and operation of coordinated ecological management system in the agriculture based on organizational, financial and economic supports. Sustainable land resources using in the agricultural sector requires: creation of the market for environmental pollution, licenses trade, financial and credit mechanism of natural resources using, environmental insurance, risk management, formation of target ecological funds, filling local budgets.